Acute Promyelocytic Leukemia in a child with Congenital Baldness: A Novel Presentation - Zawar, Asfa; Ali, Sundas; Sohail, Aliena; Jiskani, Shahzad Ali (International Journal of Pathology, 2018)
Acute leukemia is most common in adults with a worldwide incidence of 351,965 cases in 2012 with amale: female ratio of 1.4. We present the case of a 12 years old female child with congenital baldness who wasadmitted to our hospital with complaints of epistaxis, gum bleed and petechial rash. She was diagnosed as a caseof acute promyelocytic leukemia(APL) on bone marrow biopsy. This is a rare finding not previously reported inliterature.